2024
DOI: 10.32634/0869-8155-2024-378-1-118-122
|View full text |Cite
|
Sign up to set email alerts
|

Improving the safety and quality of jelly-fruit marmalade, recommendations for sweeteners

E. V. Kazantsev,
N. В. Kondratie,
O. S. Rudenko

Abstract: Relevance. Reduced calorie confectionery products, such as marmalade containing fruit raw materials, cocoa products, are included in the diet of consumers, are in high demand and are associated with healthy food products.Methods. The aim of the work is to identify patterns of changes in the quality of jelly-fruit marmalade containing sweeteners erythritol and xylitol during storage. Apple puree was used as a fruit raw material. The sweeteners erythritol and xylitol are justified for partial replacement of whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Thus, changes in the quality of jelly-fruit marmalade with the content of erythritol and xylitol sweeteners with 50 % replacement of white sugar have been established. It was found that the samples have high organoleptic and physicochemical quality indicators [26]. The use of stevia sweetener during the production of chokeberry marmalade is known.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Thus, changes in the quality of jelly-fruit marmalade with the content of erythritol and xylitol sweeteners with 50 % replacement of white sugar have been established. It was found that the samples have high organoleptic and physicochemical quality indicators [26]. The use of stevia sweetener during the production of chokeberry marmalade is known.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%